Socio-Cultural Support For The Sustainability Of Food Production And Consumption In Highland Communities In Sinjai District, South Sulawesi Province. - Ahmad, Ahfandi; Ali, Muhammad Saleh S.; Rahmadanih, Rahmadanih; Teddu, Sulaiman (International Journal of Agriculture System, 2023)
Socio-culture is increasingly recognized as an important part towards sustainable food production and consumption. This evolution is reflected in the fact that socio-culture is now generally referred to as one of the main drivers of sustainable food production and consumption. This study focuses on socio-cultural aspects in relation to the food production subsystem and food consumption subsystem in highland communities in West Sinjai District, Sinjai Regency, South Sulawesi Province. Using a qualitative approach, case study method, with data collection techniques, in-depth interviews, full observation, documentation and triangulation. So that it can see in depth the socio-cultural reality of the highland community. The socio-cultural apparatus is one of the supporting factors in the realization of the sustainability of food production and consumption in highland communities. The socio-cultural apparatus is one of the supporting factors in realizing the sustainability of food production and consumption in upland communities. The socio-cultural component in the food production of highland communities strongly emphasizes the value of togetherness, the value of mutual cooperation and religious values. These values are implemented into food production activities from land preparation to harvesting such as; "Appada Elo"; "Appatinro Bine"; "Passibaling"; "Ganre Pare Beru". The socio-cultural component of food consumption in highland communities also emphasizes religious values (a symbol of gratitude to the creator and getting closer to their ancestors), the value of togetherness (serving food to others as a form of respect and appreciation) and prestige values (types of food such as: local varieties of brown rice). These values are wrapped in community norms that have been maintained for generations as an effort to maintain the sustainability of community food production and consumption